State, Church and Values during the Ukraine Crisis: the Dynamics of Charisma in Russia and Estonia - Kilp, Alar (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
The paper applies Weberian conceptualizations of charisma in the study of contemporary war-leadership. The study analyzes political legitimacy and legitimization of war by religious and secular leaders since the full-scale invasion of Ukraine by the Russian Federation on February 24, 2022 from three perspectives: 1) pure and manufactured charisma; 2) value charisma at the charismatic moment; 3) charismatic (de)legitimation of war. The comparison of two cases - liberal democratic and authoritarian imperial, traditionally Lutheran and Orthodox - yields variations in several dimensions: legitimacy for political governments (progressive vs traditional values); religious and secular sources of sanctioning of charismatic domination; the interaction of personal and depersonalized, institutional and manufactured charisma; instrumental construction of present charisma by sacralization of historic identity, persons, events and institutions. The paper concludes with the discussion of the explanatory value of Weberian conceptualizations of charisma in the study of religious and secular leadership in war-time democratic and authoritarian contexts.